An experimental study of the role of partial melts of sediments versus mantle melts in the sources of potassic magmatism. (15th June 2019) - Förster, Michael W.; Prelević, Dejan; Buhre, Stephan; Mertz-Kraus, Regina; Foley, Stephen F.
Graphical abstract: Highlights: We simulate mantle metasomatism by reacting sediment or basanite with dunite. Sediment/dunite reaction is a precursor for K-rich magmatism with orogenic signature. The reaction of melt with refractory mantle dynamically increases K/Na ratio. K-enrichment of melts is independent from the experiments' starting composition. Abstract: Potassium-rich lavas with K/Na of >2 are common in orogenic and anorogenic intraplate magmatic provinces. However, in the primitive mantle, the concentration of Na exceeds that of K by 10 times. The source of K-rich lavas thus needs to be either K-enriched or Na-depleted to account for high K/Na ratios. The geochemical and isotopic compositions of high 87 Sr/ 86 Sr post-collisional lavas show that their mantle source contains a recycled crustal component. These highly K-enriched lavas with crustal like trace element patterns are termed "orogenic lamproites" and are compositionally distinct from K-rich "anorogenic lamproites" that show lower 87 Sr/ 86 Sr and a trace element pattern that resembles that of primary mantle melts. For both groups the processes of K-enrichment within their source are uncertain and are thought to be linked to melts of sedimentary rocks for "orogenic lamproites" and low-degree melts of ultramafic mantle rocks for "anorogenic lamproites". In both cases, metasomatism of the mantle lithosphere is the precursor to K-rich magmatism. In this study we experimentally determine the effects of mantle metasomatism by sediment- and hydrous mantle melts. The experiments simulate the interaction of refractory lithospheric mantle and metasomatizing melt in a 2-layer reaction experiment. The sediment/dunite reaction experiments lead to formation of a strongly K-enriched phlogopite-pyroxenite layer sandwiched between the two starting materials. The low temperature of the sediment/dunite reaction runs at <1000 °C simulates a fore-arc subduction environment, in which the melts of sediment are consumed during interaction with dunite as the temperature is below the solidus of the produced phlogopite-pyroxenites. The hydrous mantle melt/dunite reaction run is simulated by reacting a hydrated basanite with dunite. Since the temperature of the reaction is higher than the solidus of the resulting phlogopite-pyroxenites (1200 °C), the hydrous melt is not consumed but flows further, increasing in K2 O and K/Na as it reacts with the refractory peridotite. In both cases, melts are enriched in K and K/Na increases by crystallizing a low K and low K/Na eclogitic residue. Compositions of glass and phlogopite from both types of reactions are comparable to glasses and phlogopites found within post-collisional lavas. Since the enrichment of K within the reaction zone is strongly controlled by the formation of low K/Na and low-K residues, metasomatic enrichment of the mantle lithosphere in K does not need a highly K-enriched metasomatic agent.